DAMPAK PERTUMBUHAN EKONOMI NASIONAL TERHADAP PEMBENTUKAN GAS RUMAH KACA DAN PENURUNAN KAPASITAS SEKTOR EKONOMI DI INDONESIA: PENDEKATAN ANALISIS INPUT-OUTPUT - FRIYATNO, SUPENA; SAMIN, BUNASOR; SYAFA’AT, NIZWAR (SOCA: Jurnal Sosial Ekonomi Pertanian, 2012)
It has been proven that national economic growth which is originally expected to improve people welfare, to balance the gaps of income, to alleviate poverty and to keep the environmental stability could not accomplish the goal of economic development. The objectives of this research are: (1) to analyze the impact of national economic growth on greenhouse gases formation, especially on emission of carbon, sulphur and nitrogen, (2) to analyze the impact of greenhouse gases emission which is formed by economic activities as consequences of national economic growth on the capacity of economic sectors, especially in declining capacity on output, income, value added and employment. To prove those main objectives, the national Input-Output analysis is used in this research. The data used in this research are input-output transaction matrix year 1980, 1985, 1990, 1995 and 2000 which is published by Statistical Center Agency (BPS). Input-Output data analysis showed that with 4.24% of economic growth scenario formed carbon, sulphur, and nitrogen each equal to 3,276.6 kilo ton, 44.2 kilo ton, and 79.9 kilo ton respectively. By internalizing the price of carbon Rp 190,000 per mt, they would decline the capacity of economic sectors, such as Rp 1.4 triliun of output, Rp 187.9 biliun of income, Rp 657.2 biliun of value added and 33.728 persons of employment respectively. In conclusion, economic growth has caused the greenhouse gaseous formation, and has implication on cost of externalities on environment. Furthermore, the policies to compensate the recovery of environmental degradation are needed through some instruments of policies, such as command-and-control, and basedmarket- policies in Indonesia.
Keywords: Impact, Economic Growth, Greenhouse Gases, Capacity, Decline, Economical Sectors.